GERAKAN FEMINISME DALAM UPAYA PERDAMAIAN DI PASIFIK SELATAN - Prihadiansyah, Khansa Deryqa (Indonesian Journal of International Relations, 2023)
This article aims to describe how the values and views of feminism move in the Pacific Islands region to build peace. The concept of feminism in peacebuilding is used in qualitative research, as well as in library studies. The results of the study show that the implementation of feminist values in the women's movement in building peace in the Pacific Islands region arises due to the high number of problems women face due to inequality in conflict and everyday life. The application of feminism in peacebuilding in the Pacific Islands region is carried out alongside the traditional view of women held by Pacific Islanders, departing from the majority of movements in the Pacific region that do the same thing instead of shifting existing values. However, the biggest unresolved problem is the lack of representation of women in the legislatures of Pacific Island countries, which has encouraged the feminist movement in peacebuilding to focus on the regional level.